Substrate composition, erodibility (Cohesive Strength Meter; CSM) and undrained shear strength (vane) measurements for UK salt marsh and tidal flat habitats - Helen Brooks; Iris Moeller; Tom Spencer; Katherine Royse (PANGAEA, 2023)
This dataset comprises measurements of substrate composition (water content, organic content, carbonate content, particle size, particle density, root mass content), erodibility (Cohesive Strength Meter; CSM) and undrained shear strength (vane) from two salt marshes in the UK. The salt marshes chosen were Warton marsh, North West England and Tillingham Marsh, South East England. Four sampling sites at each marsh were chosen: tidal flat, marsh edge, creek edge and inner marsh. Samples were taken for compositional analysis at 0-10 cm, 10-20 cm and 20-30 cm at each location, with additional samples at 30-40 cm, 40-50 cm and 50-60 cm at the marsh edge location. The same sampling strategy was used for the CSM, shear vane and torvane measurements, but these could only be sampled until the water table was reached. Shear vane measurements began at 10 cm depth below the surface, as the vane paddles reached 10cm below the surface at their lowest point. At each sampling location, three replicate CSM measurements were taken, ten replicate shear vane measurements, and ten replicate torvane measurements. Samples were taken between 29th September and 1st October 2017 at Tillingham and 6th and 10th July 2018 at Warton. CSM and vane analyses were undertaken on 15th-16th October and 29th November 2018 at Tillingham, and 18th-20th October 2018 at Warton.